1989
DOI: 10.1093/intimm/1.4.409
|View full text |Cite
|
Sign up to set email alerts
|

T cell multideterminant regions in the human immunodeficiency virus envelope: toward overcoming the problem of major histocompatibility complex restriction

Abstract: Helper T cell determinants should be an important component of an anti-human immunodeficiency virus (HIV) vaccine aimed at either antibody or cytotoxic T cell immunity. However, model protein studies have raised concern about the usefulness of any single determinant, because a given determinant is likely to be seen by only a small subset of major histocompatibility complex (MHC) types within the population. Here, we use 44 peptides, including ones predicted and not predicted on the basis of amphipathicity to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Previous studies have sought to characterize immunogenic peptides from the HIV envelope (env) protein (13)(14)(15)(16)(17)(18)(19)(20) for a variety of mammalian species expressing a spectrum of MHC class II phenotypes. Much of the available information was generated by scoring heterogeneous CD4 ϩ T cell responses in bulk proliferation assays (13,15,16,18). Some of these responses were very weak, and the assignment of antigenic epitopes from such studies to almost every region of the HIV env protein is open to question.…”
mentioning
confidence: 99%
“…Previous studies have sought to characterize immunogenic peptides from the HIV envelope (env) protein (13)(14)(15)(16)(17)(18)(19)(20) for a variety of mammalian species expressing a spectrum of MHC class II phenotypes. Much of the available information was generated by scoring heterogeneous CD4 ϩ T cell responses in bulk proliferation assays (13,15,16,18). Some of these responses were very weak, and the assignment of antigenic epitopes from such studies to almost every region of the HIV env protein is open to question.…”
mentioning
confidence: 99%
“…Both I-E k and I-A s present T1 and PCLUS 3, but only I-E k , not I-A s , binds the Ala-substituted peptide with higher affinity (8,21,39). The CTL response to P18IIIB-pulsed targets was significantly better in A.AL mice expressing the relevant I-E k class II allele (P Ͻ 0.05, Tukey-Kramer HSD test) whereas no difference in CTL induction was found in A.TH mice expressing I-A s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A limited understanding of the extent of sequence variability that can be tolerated by class II molecules before immune reactivity to defined epitopes is abolished currently exists, and this is the first study to compare Env viral sequences to functional T-helper cell responses in HIV-1 subtype C infected children. The selection of the HIV-1 stimulus used in this study was based on previous reports which had identified these peptides to be broadly immunogenic across MHC haplotypes [28][29][30], and which have documented T-helper cell responses to these peptides in several, independent populations of HIV-1 exposed, uninfected individuals [31][32][33][34]. The P18 MN and P18 IIIB variable regions of the virus isolates showed considerable amino acid variation from the peptides used for in vitro stimulation and it seems unlikely that these peptides would have been recognised.…”
Section: Discussionmentioning
confidence: 99%